A Microclimate Monitor Sensor Network with an Effective Data Aggression Algorithm - Chen, Li Ping; Du, Shang Feng; Xu, Gang; Zhang, Rui Rui; Kan, Jie (Applied Mechanics and Materials, 2014)
Wireless sensor network technology has the potential to reveal fine-grained, dynamic changes in monitored variables of outdoor landscape. But there are significant problems to be overcome in order to realize the vision in working systems, such as effective utilize of energy, prolong network life and improve sensor accuracy. This paper describes the design and evaluation of a sensor network with an effective data aggression algorithm applied in orchard microclimate monitor. A novel feature of the solution is its data compression algorithm design, in which all sensors were encoded with Morton code and a logical multi-lays cluster was constructed among the nodes. Making use of the similarity of the output of the sensors, the algorithm reduces network data amount and power cost significantly to prolong life of the network. Tests and experiments results are shown in diagrammatic form. The system was field tested over one month in Nankou farm located in Beijing province of China. The experimental results demonstrate that effective collecting of environmental information can be achieved by using our proposed system.